Intertwingled The Work and Influence of Ted Nelson - Dechow, Douglas R.; Struppa, Daniele C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This engaging volume celebrates the life and work of Theodor Holm (3z(BTed(3y (BNelson, a pioneer and legendary figure from the history of early computing. Presenting contributions from world-renowned computer scientists and figures from the media industry, the book delves into hypertext, the docuverse, Xanadu, and other products of Ted Nelson$1 (Bs unique mind. Topics and features: Includes a cartoon and a sequence of poems created in Nelson$1 (Bs honor, reflecting his wide-ranging and interdisciplinary intellect Presents peer histories, providing a sense of the milieu that resulted from Nelson$1 (Bs ideas Contains personal accounts revealing what it is like to collaborate directly with Nelson Describes Nelson$1 (Bs legacy from the perspective of his contemporaries from the computing world and the scholars who continue to examine his work Provides a contribution from Ted Nelson himself With a broad appeal spanning practitioners in computer science, historians of science and the general reader, this inspiring collection reveals the continuing influence of the original visionary of the World Wide Web. Prof. Daniele C. Struppa is Chancellor of Chapman University, Orange, CA, USA. His other publications with Springer include the titles The Mathematical Legacy of Leon Ehrenpreis and Noncommutative Functional Calculus. Dr. Douglas R. Dechow is Digital Humanities and Science Librarian at Chapman University Leatherby Libraries.s
Part I: Artistic Contributions -- The Computer Age -- Odes to Ted Nelson -- Part II: Peer Histories -- The Two-eyed Man -- Ted Nelson$1 (Bs Xanadu$1 (BCaution: Four Letter Words Ahead -- Hanging Out with Ted Nelson -- Riffing on Ted Nelson$1 (BHypermind -- Intertwingled Inspiration -- An Advanced Book for Beginners -- Part III: Hypertext and Ted Nelson-Influenced Research -- The Importance of Ted$1 (Bs Vision -- Data, Metadata and Ted -- Making Links: Everything Really is Deeply Intertwingled -- Ted Nelson -- History Debugged -- We Can and Must Understand Computers NOW -- The Future of Transclusion -- Ted Nelson: A Critical (and Critically Incomplete) Bibliography -- Part IV: The Last Word -- What Box?.s
Keywords: Computers -- History; Digital humanities; Artificial intelligence -- Data processing; User interfaces (Computer systems).; Human-computer interaction; History of Computing; Digital Humanities; Data Science; User Interfaces and Human Computer Interaction